Shifting baselines : (Island Press, 2011)
Shifting Baselines explores the real-world implications of a groundbreaking idea: we must understand the oceans of the past to protect the oceans of the future. In 1995, acclaimed marine biologist Daniel Pauly coined the term "shifting baselines" to describe a phenomenon of lowered expectations, in which each generation regards a progressively poorer natural world as normal. This seminal volume expands on Pauly's work, showing how skewed visions of the past have led to disastrous marine policies and why historical perspective is critical to revitalize fisheries and ecosystems.